Optimization The Effectiveness Of Universities Financial Statement Using Cloud Accounting - Harahap, Aulia Rahman (International Conference on Sciences Development and Technology, 2022)
When the development of the digital era 4.0 has explored all fields, both in education, technology and other fields. In terms of financial statements, it is felt that at this time they must follow these developments. In terms of facilitating a job and the risk is quite risky. In universities, in a financial report, one of which is the balance sheet, it is still not optimal for the leadership. The report is in the form of a balance sheet report at Raharja College. This study faces 2 (two) problems, namely the manual calculation of the balance sheet and high errors. This can hinder financial reports to the leadership every month. In preventing these problems, good and appropriate financial report management is needed. Cloud accounting is the use of the cloud as an online accounting storage. With the use of cloud accounting in the online journal.id software, income and expenditure data has been inputted properly, so that the balance sheet data is accurate and fast. There is a report menu on journal.id to get overall and accurate Balance Sheet data. There are 7 (seven) methods as problem solving used in this research. Researchers hope that the management of balance sheet financial statements can make it easier for accountants to submit reports to the leadership every month. There are 7 (seven) methods as problem solving used in this research. Researchers hope that the management of balance sheet financial statements can make it easier for accountants to submit reports to the leadership every month. There are 7 (seven) methods as problem solving used in this research. Researchers hope that the management of balance sheet financial statements can make it easier for accountants to submit reports to the leadership every month.